Fecal Transmission of Spodoptera frugiperda Multiple Nucleopolyhedrovirus (SfMNPV; Baculoviridae) - Eduardo Ávila-Hernández; Cindy S. Molina-Ruiz; Juan S. Gómez-Díaz; Trevor Williams (Viruses)
The production of viable nucleopolyhedrovirus in the feces of infected lepidopteran larvae represents a poorly understood route for virus transmission prior to host death. In the present study, we examined the presence of viable virus in the feces of fourth-instar Spodoptera frugiperda larvae infected with the Nicaraguan isolate of Spodoptera frugiperda multiple nucleopolyhedrovirus (SfMNPV-NIC). Feces production increased in samples taken at 2 to 6 days post-inoculation but was significantly lower in infected insects compared to controls. Second instars experienced 3.9 to 68.3% of polyhedrosis disease following consumption of feces collected at 2–5 days post-inoculation, which subsequently fell to 29.1% in the 6-day sample. Calibration of the insect bioassay using OB-spiked samples of feces indicated that the concentration of OBs varied between 5.4 × 102 and 4.4 × 105 OBs/100 mg of feces in infected fourth instars. Quantitative PCR analysis of fecal samples indicated the presence of 0 to 7629 copies/mg feces following amplification targeted at the polyhedrin gene. However, no correlation was detected between qPCR estimates of virus concentration and time of sample collection or the quantity of feces collected. The qPCR estimates were positively correlated with the prevalence of lethal infection observed in the insect bioassay, but the correlation was weak and several samples did not amplify. Calibration of the qPCR assay using OB-spiked samples of feces provided estimates that were 5- to 10-fold lower than the insect bioassay, indicating inhibition of the amplification reaction or loss of material during processing. In a greenhouse experiment, 2.5–48.3% of second-instar larvae acquired lethal infection following a 24 h period of feeding on maize plants on which fourth instar larvae had deposited their feces at 3 days and 4 days post-infection, respectively. These findings highlight the potential of OB-contaminated feces as a source of biologically significant quantities of inoculum for virus transmission prior to the death of infected insects and represent an additional contribution to the biological control of lepidopteran pests by these pathogens.